Recent Development of Carbon Nanotube Transparent Conductive Films - Yu, LePing; Shearer, Cameron; Shapter, Joseph (Chemical reviews, 2016)
Transparent conducting films (TCFs) are a critical component in many personal electronic devices. Transparent and conductive doped metal oxides are widely used in industry due to their excellent optoelectronic properties as well as the mature understanding of their production and handling. However, they are not compatible with future flexible electronics developments where large-scale production will likely involve roll-to-roll manufacturing. Recent studies have shown that carbon nanotubes provide unique chemical, physical, and optoelectronic properties, making them an important alternative to doped metal oxides. This Review provides a comprehensive analysis of carbon nanotube transparent conductive films covering detailed fabrication methods including patterning of the films, chemical doping effects, and hybridization with other materials. There is a focus on optoelectronic properties of the films and potential in applications such as photovoltaics, touch panels, liquid crystal displays, and organic light-emitting diodes in conjunction with a critical analysis of both the merits and shortcomings of carbon nanotube transparent conductive films.